ANALISIS VEGETASI JENIS POHON PANTAI DI NEGERI HATU - Syahrul, Muhammad; Arini, Ine; Muskitta, Marike (Program Studi Pendidikan Biologi FKIP Unpatti, 2025)
Background: The coastline of Negeri Hatu in Central Maluku Regency harbors a diverse tree vegetation ecosystem that plays a critical role in maintaining environmental stability and mitigating coastal erosion. This study aims to analyze the structure and composition of tree vegetation in the Negeri Hatu beach area. Methods: The research employed the quadrat transect method with purposive sampling to observe diversity, density, dominance, and evenness of vegetation. Results: The results showed the presence of 7 tree species from 7 different families, with a Shannon-Wiener diversity index (H') value of 3.071, indicating moderate species diversity. Coconut trees (Cocos nucifera) had the highest Importance Value Index (IVI) at 36.39%, signifying their significant ecological role in maintaining the stability of the coastal ecosystem. Species distribution was relatively even, with low dominance levels. Conclusion: The study concludes that conserving coastal vegetation is crucial for maintaining the balance of coastal ecosystems and mitigating environmental impacts.